Perancangan Sistem Lelang Online Handphone Second Berbasis Web Menggunakan Metode Rapid Application Development (RAD) - Bimo Wicaksono (CV. Multi Kreasi Media, 2023)
As today's technological advances have taken place, communities, especially the younger generation, are making great efforts to keep up with the latest in mobile phones. However, most of them are in the lower middle-class economy, while those who want to meet their gangs to participate in technological development. There is another option of keeping up with the latest updates without spending too much money, such as the trend on cell phone second. At a fraction of a new price, they can get a whole range of brand phones as well as specs capable of keeping up with the present day. This online auction system is designed to eliminate the problems of sales of conventional second phones, buyers must come to the site to look for second phones, not to mention the bargain that often doesn't fit the budget. The online auction application system uses PHP programming language, MySQL for database and USES the Rapid Application Development (RAD) methods. The whole thing is to make it easier for the seller or the second cell phone buyer without getting hit by the distance and the price.